Chronic periodontitis, preeclampsia and serum Interleukin-8: Is there a link? - Sadiqa, Ayesha; Cheema, Abdul Majeed (Pakistan Journal of Physiology, 2019)
Background: Association of periodontitis with preeclampsia through mediators has currently been in consideration. Present study aimed to compare serum IL-8 levels in normotensive and preeclamptic gravid women with and without chronic periodontitis in antepartum and postpartum phases. Methods: It was a longitudinal cohort study of pregnant women of Narowal aged 18?34 years. Thirty subjects had normal periodontium (6 preeclamptics+24 normotensives), while 40 had periodontitis (6 preeclamptics+34 normotensives). Blood samples were first taken in antepartum and again in postpartum phase of the same women. Periodontium assessment by CPITN probing and preeclampsia verification was done. IL-8 estimation was done using ELISA. Results: Periodontally healthy normotensives exhibited 4% raised IL-8 in ante partum while preeclamptics showed increased IL-8 by 0.04% postpartumly. Periodontitis with normotensives showed 46% increased IL-8 in postpartum whereas periodontitis with preeclampsia showed 10% high IL-8 in antepartum. In antepartum, normotensives periodontitis revealed 1% increased IL-8 while normotensives with healthy periodontium revealed 14% increased IL-8. In postpartum normotensives, with periodontitis exhibited 62% more IL-8 while normotensives with healthy periodontium revealed 10% more IL-8. In antepartum, normotensives with healthy periodontium exhibited 2.3% raised IL-8 while preeclamptics with periodontitis showed 11% raised IL-8. In postpartum normotensives with periodontitis showed 49% more IL-8 while periodontally healthy preeclamptics showed 0.5% more IL-8. Conclusion: Raised serum IL-8 levels were observed in normotensives affected with chronic periodontitis and those who were with healthy periodontium in antepartum and postpartum phases. Highest serum IL-8 was observed in normotensives with chronic periodontitis in their postpartum phase. Pak J Physiol 2019;15(3):53–6